Estudio de prefactibilidad para la instalación de una planta productora de crema hidratante a base de aceite de coco y espirulina - Arellano Cardenas, Jesus (2023)
Nowadays, there is an existing growing trend about personal image care, being personal skin care one of the most important and influential aspects of the industry. For that reason, we propose the realization of a moisturizer of spirulina and coconut oil which provides many benefits to the skin and is composed of much healthier ingredients. This research work is based on 8 fundamental chapters, with the purpose of determining the viability and feasibility of the study. The first chapter explains the objectives of the research, the justification of its implementation and hypothesis. The second chapter details the market study and calculation of the project’s demand, through the application of surveys and the utilization of information sources, where a demand of 41 623 bottles was obtained for 2026. The chapter 3 and 4 focus on the location and size of the processing plant, which will be located in Villa El Salvador (Lima) and will have a size of 41 623 bottles. As for the fifth chapter, it explains in more detail the production process of the moisturizer and its requirements, plant capacity and layout, supply chain design and maintenance; also, chapter 6 focuses on the organizational scheme of the company. Finally, chapters 7 and 8 evaluate the various economic, financial and social aspects involved in the project implementation, where the viability of the project is demonstrated, since an NPV of S/ 44 973 with an internal rate of return of 25,29% is obtained. At the end of the eight chapters, the conclusions and recommendations are mentioned, in order to be able to make a better feedback of the final results.